STABILITY OF PARTIAL NITRITATION OF POULTRY SLAUGHTERHOUSE WASTEWATER IN A SEQUENTIAL BATCH REACTOR - Assis,Tatiane M. de (2017)
ABSTRACT The aim of this study was to monitor the stabilization of a sequential batch reactor (SBR) regarding the partial nitritation of poultry slaughterhouse wastewater, aiming at preparing it for a reactor with bacteria that promote anaerobic ammonia oxidation (anammox). A cylindrical reactor with a useful volume of 3.5 L, mechanical agitation (50 rpm), and suspended biomass was used in the experiment. The strategies adopted for nitrite-oxidizing bacteria (NOB) inhibition were cycle time (CT: 24, 16, 6, 5, 4 h and real-time monitoring), free ammonia accumulation, alkalinity restriction and low concentrations of dissolved oxygen (DO). The ammonification process, observed at all experimental phases, negatively influenced the control of partial nitritation process. Alkalinity restriction under low cycle times (4 and 5 h) conditions, together with low dissolved oxygen concentration, was a key factor for nitrite-oxidizing bacteria inhibition. Stability of partial nitritation was only reached by real-time monitoring, being the cycles stopped when 50% N–NH4+ and 50% N–NO2− were present in the reactor.